Indicator of “Temukan” Model For Stop HIV Program in Blitar City - Wiwin Martiningsih; Sri Winarni; Suprajitno Suprajitno; Engelina Choiru Fitroti (Health Gate, 2026)
Achieving the "Three Zeros" target (zero new infections, zero related deaths, and zero discrimination) for the HIV/AIDS program in Blitar City remains a challenge. Specifically, the target of 95% of People Living with HIV/AIDS (PLWHA) knowing their status has not yet been achieved. This research aims to describe the indicators of the "Temukan” strategy as part of the STOP (Suluh-Temukan-Obati-Pertahankan / Educate-Seek-Treat-Retain) acceleration program. A qualitative design was employed, and data were collected through Focus Group Discussions (FGDs) and in-depth interviews with 12 informants, including PLWHA, community cadres, health workers, and policymakers. Data were analyzed using OpenCode software, which identified five primary indicators categorized into: inputs for "Temukan" or seek activities in “STOP” strategy, processes (including workflow, cross-sectoral coordination, and implementation), and outputs (including increased coverage, improved quality of life for PLWHA, and program sustainability). These findings serve as an evaluation tool and a basis for policymaking in HIV/AIDS prevention.